Bart Lodewijks : Looking for a beautiful place. - Serafijn, Q.S. (Amsterdam : Roma Publications Amsterdam, 2003)
This book shows a series of works realized by Bart Lodewijks during a two years stay in Glasgow, Scotland, 2000-2002. All photographs are taken by the photographer and friend Huig Bartels. The Highland works are part of a collaborative project by Bartels and Lodewijks.
Engels
Nederlands
boek
Keywords: Lodewijks, Bart